Women and nature: An ecofeminist study of environmental conservation sustainability - Bilqis Amelia Devi Chinsya; Zohaib Hassan Sain (An-Nisa’ Journal of Gender Studies, 2024)
Amid the global climate crisis, women who are disproportionately affected by environmental degradation are often excluded from ecological decision-making. Environmental exploitation coincides with the marginalization of women within patriarchal structures. As forests vanish and water becomes polluted, women’s voices are silenced. The purpose of this study is to analyze the structural roots of patriarchy in ecological crises and the central role of women in environmental conservation for sustainability. Using an integrative critical literature review combined with in-depth interviews, secondary and primary data were thematically analyzed through triangulation to identify conceptual patterns, patriarchal power relations, and women’s ecological knowledge in promoting environmental sustainability. The findings indicate that, first, patriarchy operates through structural mechanisms that constitute the shared root of gender inequality and ecological crises. Second, environmental exploitation represents the most dominant issue, accompanied by significant impacts and the subordination of women. Third, ecofeminism positions women as key actors in conservation, where women-led initiatives reduce environmental degradation while simultaneously empowering women. This study concludes that patriarchy constitutes the structural root of ecological crises; however, women-led conservation efforts can reduce environmental degradation while simultaneously strengthening women’s empowerment. This study contributes to strengthening ecofeminism empirically by demonstrating gender inequality as a mediating factor and by proposing integrative policy recommendations.